Loss of pigment epithelium derived factor expression in glioma progression. Issue 4 (1st April 2003) - Guan, M; Yam, H-F; Su, B; Chan, K-P; Pang, C-P; Liu, W-W; Zhang, W-Z; Lu, Y
Abstract : Background: Pigment epithelium derived factor (PEDF) was first isolated from medium conditioned by human fetal retinal pigment epithelial cells. PEDF was detected in a broad range of human fetal and adult tissues including almost all brain areas. It can also inhibit the proliferation of cultured rat astrocytes. Recent studies have implicated PEDF in activities that are inhibitory to angiogenesis. Aims: To investigate the expression of PEDF in gliomas to assess its "gliastatic" effects and its role in anti-angiogenesis. Methods: PEDF mRNA values were measured by quantitative real time reverse transcription polymerase chain reaction (RT-PCR) analysis of normal brain tissue and tumour specimens from both low and high grade gliomas. In addition, immunohistochemical staining for PEDF and vascular endothelial growth factor (VEGF) was performed on 32 paraffin wax embedded glioma samples, 10 of them grade IV, 10 grade III, seven grade II, and five grade I. Results: RT-PCR showed that PEDF mRNA values were 5.0 (p < 0.001) and 15.4 (p < 0.001) times higher in normal human brain specimens (n = 5) than in tumour tissue specimens of low grade glioma (grades I and II; n = 15) and high grade glioma (grades III and IV; n = 10), respectively. VEGF was strongly positive in 90% of grade IV, 70% of grade III, 43% of grade II, and 20% of grade I cases. In contrast, PEDF was positive in none of grade IV, 20% of grade III, 43% of grade II, and 60% of grade I tumours. There was an inverse correlation between VEGF and PEDF expression, and a lack of PEDF in advanced grade gliomas. Conclusions: It is possible that the absence of PEDF expression is a potent factor for the enhancement of angiogenesis in glioma.